Regional Airport Expansion: Expansions of Regional Airports and their Effect on the Local Economy - Philipp Breidenbach (European Regional Science Association (ERSA), 2015)
This paper exploits the deregulation of the European aviation market as a quasi-natural experiment to examine if the expansion of regional airports in Germany caused positive spillover effects on the surrounding economy. Such spillovers might justify the heavy subsidies which are transferred to airports annually. Standard evaluations of infrastructure investments have to face reverse causality problems since the investment decisions are based on the regional conditions of the regional economy. The deregulation act forms a exogenous incentive to invest in the expansion of existing regional airports. Furthermore, most of these airports act as military base and their location is not economically driven. Under these circumstances a Difference in Differences approach allows to estimate causal effects of the expansion on the regional growth. Following this identification strategy, the results are sobering since airport expansions are not found to have any positive spillover effect on regional growth.
Keywords: R51; R42; H54; 330; Infrastructure investment; Regional growth; Airport effects